2015
DOI: 10.1002/hbm.22861
|View full text |Cite
|
Sign up to set email alerts
|

Persistency and flexibility of complex brain networks underlie dual‐task interference

Abstract: Previous studies on multitasking suggest that performance decline during concurrent task processing arises from interfering brain modules. Here, we used graph-theoretical network analysis to define functional brain modules and relate the modular organization of complex brain networks to behavioral dual-task costs. Based on resting-state and task fMRI we explored two organizational aspects potentially associated with behavioral interference when human subjects performed a visuospatial and speech task simultaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 102 publications
1
36
0
Order By: Relevance
“…Crucially, connector nodes are also not involved in all betweenmodule connectivity. Nonconnector node regions play a role as well (28,87,93,94), and, as noted above, increased betweenmodule connectivity that is not routed through connector nodes has been found during many different tasks, and differentiates task connectivity from resting-state connectivity (36). Although the current and previous findings suggest that connector node regions coordinate some of these between-module connections, it is likely that other mechanisms for between-module communication exist that are executed by nonconnector nodes.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…Crucially, connector nodes are also not involved in all betweenmodule connectivity. Nonconnector node regions play a role as well (28,87,93,94), and, as noted above, increased betweenmodule connectivity that is not routed through connector nodes has been found during many different tasks, and differentiates task connectivity from resting-state connectivity (36). Although the current and previous findings suggest that connector node regions coordinate some of these between-module connections, it is likely that other mechanisms for between-module communication exist that are executed by nonconnector nodes.…”
Section: Discussionsupporting
confidence: 48%
“…However, the membership changes of connector node regions (i.e., brain regions identified as connectors in our analysis) was only associated with an increase in performance. Moreover, the high-performing subjects (i.e., subjects with connector nodes that changed module membership) had less connectivity between single-task modules (i.e., more modular) (83). Another fMRI study found that increased module membership changes of 11 regions, 7 of which are connector node regions in our analysis, predicted increased learning rates (87).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…The non‐smoothed functional volumes were further investigated to avoid spuriously high correlations between time‐series from the neighboring ROIs [Alavash et al, ; Cole et al, ; Fornito et al, ]. We used CONN Functional Connectivity Toolbox v. 15.f (http://www.nitrc.org/projects/conn/, [Whitfield‐Gabrieli and Nieto‐Castanon, ]) to perform the denoising of the functional time series and to create pairwise correlation matrices.…”
Section: Methodsmentioning
confidence: 99%
“…Functional connectivity operates dynamically on both spatial and temporal scales, which is thought to promote adaptation to changing neural demands and allow for network reconfiguration across behavioral states (Cole et al, 2013; Allen et al, 2014; Alavash et al, 2015; Davison et al, 2015). Task-state fMRI studies investigating learning, memory, and working memory have shown that more dynamic connectivity during task execution, particularly of the FPN and DMN, relates to better cognitive performance (Bassett et al, 2011; Fornito et al, 2012; Spreng and Schacter, 2012; Cole et al, 2013; Monti et al, 2014; Beaty et al, 2015; Braun et al, 2015; Vatansever et al, 2015b).…”
mentioning
confidence: 99%